Knowledge retention at the University of Limpopo's research administration and development in the Limpopo Province of South Africa - Ngwepe, Lesiba Johannes (My University, 2023)
Knowledge retention (KR), among research departments at higher education institutions throughout the world, has developed into the most important and crucial element for preserving knowledge. The study was conducted at the University of Limpopo research's Department of Research Administration and Development (DRAD) in the Limpopo Province of South Africa. The objectives of the study were to: Identify strategies used at the UL‘s DRAD to retain knowledge, establish the role of ICTs as tools and enablers of KR, assess the impact of knowledge loss at the UL‘s DRAD, to determine the barriers of KR within the UL‘s DRAD and to propose strategies that can improve KR at the UL‘s DRAD. This study used a qualitative research approach guided by a conceptual framework derived from the following theories: The KR Framework, the Theory of Organizational Knowledge Conversion, and the Model for Improving Higher Education Research Output, along with an interpretivist paradigm, which works well in qualitative studies. Total population sampling, also known as non-probability sampling, was employed to sample 13 research officials and 5 HR managers. Given the COVID-19 requirements and regulations, the researcher conducted interviews by phone, Zoom, Google Meet, or online questionnaires, depending on the respondent's convenience. Thematic analysis was used to analyse the data. The found that UL‘s DRAD use e-mail, computers/ laptops, ITS enabler, workshops, seminars, and internet and intranets as strategies to retain knowledge. The study also found that ICTs is a great enabler of knowledge retention and optimisation of daily duties at UL‘s DRAD. Moreover, the study established that the impact of knowledge loss at UL's DRAD result in unrecovered expertise. As a results, the researcher recommends the UL‘s DRAD should put in place knowledge recovery initiatives to deal with the consequences of knowledge loss and stop further occurrences. Other results indicate that UL‘s DRAD encounters barriers in storing and sharing employees‘ knowledge. The impediments are a lack of knowledge storage systems and databases to store knowledge of the employees. These impediments have been found to negatively affect the performance of the UL‘s DRAD officials‘ duties, since there is lack of knowledge and expertise transfer between co-workers. Proposed KR strategies which are needed to improve KR were identified as linking ICTs to with the UL's DRAD employees, putting organisational knowledge on electronic databases and HRM initiatives (Performance appraisals and employee rewards). Therefore, the researcher recommends that the UL's DRAD to employ these strategies to maintain the staff as well as the knowledge that their people have acquired.
Thesis (M. (Information Studies)) -- University of Limpopo, 2023
Keywords: knowledge retention; Knowledge loss; Knowledge management; Human resource practices; Research Administration and Development; University of Limpopo; Knowledge management; Intellectual capital; Public administration -- Research